UN ÍNDICE PARA LA EVALUACIÓN DEL HÁBITAT DE AGOUTI TACZANOWSK/1 (RODENTIA: AGOUTIDAE) EN ÁREAS DE BOSQUE ANDINO NUBLADO - Pérez Torres, Jairo; Unidad de Ecología y Sistemática (UNESIS), Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
This paper presents an index to evaluate the habitat of Agouti taczanowskii in high mountain cloud forests. Theobjective of this index is to obtain arguments for decision-makers for management and design of reserves for thisspecies. This index is based on both qualitative and quantitative criteria that result in a habitat's quality value foreach habita! evaluated. Different values of the index can then be compared among different habitats, in order tovalue hierarchically which habitat is the best for management or for conservation. The index is based on twelveimportan! variables for the persistence of this species: percent of habita! use, abundance, human exploitation,leve! of protection, number of plant species in the diet, foliage cover, accessibility to plant species used for thediet, potential areas for reproduction and breeding, availability of water resources, habita! heterogeneity andpresence of predators and/or competitor species.